Penerapan Metode Image-to-Speech melalui Kamera dalam Aplikasi berbasis Kecerdasan Buatan untuk Orang dengan Disleksia - Bryan; Aprillio, Daniel; Atmadjaja, Anna Bella; Wijaya, Mychael; Saputri, Theresia Ratih Dewi (Teknik Informatika Universitas Pamulang, 2024)
Dyslexia occurs worldwide despite the culture or language. Dyslexia affects about 9% - 12% of the population, with 2% - 4% of the population experiencing significant reading impairments. This research aims to develop an artificial intelligence-based application using the Image-to-Speech method that can convert digital text into audible sound for individuals with dyslexia without requiring their brain to process the writing. This method can assist people with dyslexia in daily life challenges such as reading traffic signs, books, or documents. Results from 10 experiments on the implementation of the proposed method indicate that individuals with dyslexia can scan the text they want to read using a camera from a smartphone or laptop. The expirements also shows that the application can convert text in image form into sound comprehensible to those with dyslexia, thus facilitating their recognition of digital writing with 90% accuracy. The application also demonstrates efficiency in terms of data processing time. The average time required for image to audio conversion is 0.22 seconds, with an average memory usage of 163.2 MiB.